2001
DOI: 10.1034/j.1600-0706.2001.920206.x
|View full text |Cite
|
Sign up to set email alerts
|

Predation and dispersal of large and small seeds of a tropical palm

Abstract: Seed size may vary greatly among individuals within plant species. What effects the extremes of this variation have for seeds taken by small mammals are poorly understood. Not all seeds removed by small mammals are necessarily eaten. Small rodents are common seed predators, but they may disperse a significant proportion of seeds by scatter hoarding them via burial. Size‐dependent predation and dispersal of seeds has not been directly tested within a plant species for tropical rodents. This study tested whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
1
16

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(129 citation statements)
references
References 76 publications
6
106
1
16
Order By: Relevance
“…Indeed, small rodents and squirrels disperse the seeds of A. mexicanum (40). In Belize, up to 30% of A. mexicanum seeds removed by mice were buried in the ground but subsequently germinated (41). Similar behavior has been observed in agouties that remove seeds of Astrocaryum standleyanum in Barro Colorado Island (42).…”
Section: Resultsmentioning
confidence: 56%
“…Indeed, small rodents and squirrels disperse the seeds of A. mexicanum (40). In Belize, up to 30% of A. mexicanum seeds removed by mice were buried in the ground but subsequently germinated (41). Similar behavior has been observed in agouties that remove seeds of Astrocaryum standleyanum in Barro Colorado Island (42).…”
Section: Resultsmentioning
confidence: 56%
“…Several studies have found that the risk of predation by insects or small mammals increases with seed size (Thompson 1987;Reader 1993;Moegenburg 1996;Brewer 2001; but see Eriksson 1999) However, a recent model of the co-evolution of seed size and seed predation (Geritz 1998) predicts an evolutionary stable strategy consisting of a continuous range of seed sizes, with small seeds tending to be attacked more frequently than large seeds. In our system, we observed little or no correlation between rates of insect attack and propagule size.…”
Section: Discussionmentioning
confidence: 99%
“…fat or tannin content) can alter this general pattern (Xiao & Zhang 2006;see below). Larger nuts and seeds are usually carried greater distances to cache sites (Hallwachs 1986;Vander Wall 1995;Jansen et al 2002Jansen et al , 2004Xiao et al 2004Xiao et al , 2005aTakahashi et al 2007;Zhang et al 2008); however, a few studies (Brewer 2001;Xiao et al 2004) have failed to observe this behaviour. Large nuts also have longer residence times in caches ( Jansen et al 2002), and large nuts often demonstrate increased fitness ( Jansen et al 2004).…”
Section: Size and Nutritional Content Of Propagulesmentioning
confidence: 99%